Abnormal expression of Rab27B in prostatic epithelial cells of benign prostatic hyperplasia alters intercellular communication. (February 2021) - Dai, Yu; Ai, Bo; Liu, Ying; Pascal, Laura E.; Wang, Zhou; Dhir, Rajiv; Sun, Xuegang; Jiang, Yu
Abstract: Abnormal intraglandular stromal-epithelial interactions have been known as a main key contributing factor for development of Benign Prostatic Hyperplasia (BPH). However, the underlying mechanism for the dysregulated intercellular communication remains unclear. In this study we compared the proteomic profiles of hyperplastic tissue with adjacent normal tissue of BPH and identified Rab27B small GTPase, a key regulator of exocytosis, as a protein that was overexpressed in the epithelium of BPH tissue. Overexpression of Rab27B in prostatic epithelial cells strongly increased the signaling activities of the PI3K/AKT and ERK1/2 pathways, whereas, downregulation of Rab27B expression in the epithelial cells of BPH reduced the signaling activities and decreased cell proliferation. The elevated Rab27B expression caused an overall increase in cell surface presentation of growth factor receptors without affecting their expression. However, the small GTPase also possesses an inhibitory activity against mTORC1 independent of its role in cell surface presentation of growth factor receptors. Our findings demonstrate a pivotal role of the small GTPase in autocrine and paracrine signaling and suggest that its abnormal expression underlies the dysregulated stromal-epithelial interactions in BPH.